Clozapine-Induced Late Agranulocytosis and Severe Neutropenia Complicated with Streptococcus pneumonia, Venous Thromboembolism, and Allergic Vasculitis in Treatment-Resistant Female Psychosis - Christina Voulgari; Raphael Giannas; Georgios Paterakis; Anna Kanellou; Nikolaos Anagnostopoulos; Stamata Pagoni (Case Reports in Medicine)
Clozapine is a second-generation antipsychotic agent from the benzodiazepine group indicated for treatment-resistant schizophrenia and other psychotic conditions. Using clozapine earlier on once a case appears to be refractory limits both social and personal morbidity of chronic psychosis. However treatment with second-generation antipsychotics is often complicated by adverse effects. We present a case of a 33-year-old Caucasian woman with a 25-year history of refractory psychotic mania after switching to a 2-year clozapine therapy. She presented clozapine-induced absolute neutropenia, agranulocytosis, which were complicated by Streptococcus pneumonia and sepsis. Clozapine-induced thromboembolism of the common femoral and right proximal iliac vein, as well as allergic vasculitis, was diagnosed. She achieved full remission on granulocyte-colony stimulating factor and specific antibiotic treatment. Early detection of severe clozapine-induced absolute neutropenia and agranulocytosis enabled the effective treatment of two among its most severe complications. Additional evidence to the previously reported possible causal relation between clozapine and venous thromboembolism is offered. Finally, clozapine-induced allergic vasculitis is confirmed as a late adverse effect of clozapine therapy.